The COVID-19 lockdown as a model of detraining in division 1 college softball players - Giorgio Zeppieri; Cheng-Ju Hung; Marissa Pazik; Michael Moser; Kevin Farmer; Federico Pozzi (BMC, 2024)
Abstract Background The COVID-19 pandemic interrupted the organized training of softball players, similar to the abrupt cessation of sports participation that can happen after an injury. Thus, the COVID-19 pandemic offers a unique model to study how sudden detraining influences softball players. Methods We recruited a sample of convenience of National Collegiate Athletic Association Division 1 softball players. They participated in three data collections: pre-lockdown (Jan 2020, T1), post-lockdown (Sept 2020, T2), and before the 2021 season (Jan 2021, T3). Between T1 and T2, players received an at-home conditioning and throwing program, but compliance was not strictly monitored. Between T2-T3, players resumed formal fall training (team-organized workouts, on-field practice, and within-team scrimmage games). At each time point, we collected bilaterally: 1) shoulder internal rotation (IR) and external rotation (ER) range of motion (ROM); 2) shoulder IR and ER strength; 3) hip IR and ER ROM; and 4) hip abduction and extension strength. We used four independent (2 Sides × 3 Timepoints) MANOVA with repeated measures; we followed up significant MANOVA main effect of time with Sidak posthoc tests for pairwise comparisons between time points. Results Fifteen players participated in this study. We found a significant MANOVA main effect of time for shoulder and hip ROM (p < 0.01). Between T1-T2, dominant shoulder ER ROM decreased 6.5°, dominant shoulder IR ROM increased 4.3°, and lead hip IR ROM increased 4.4°. Between T2-T3, dominant shoulder ER ROM increased 6.3° and trail hip ER ROM increased 5.9°. We found a significant MANOVA main effect of time for shoulder strength (p = 0.03) but not for hip strength (p = 0.18). Between T2-T3, non-dominant shoulder IR and ER increased 1.8 kg and 1.5 kg, respectively. Conclusion A sudden and prolonged cessation of organized training generated changes in shoulder and hip ROM but affected strength to a lesser extent. The loss of shoulder ER and increased lead hip IR ROM are maladaptive as they are associated with injury in overhead athletes. Resuming team-organized training and scrimmage reversed some (shoulder ER), but not all of these changes. Practitioners should monitor clinical variables regularly and be aware of potential changes due to unexpected and prolonged interruptions in training, such as when players suffer sports-related injuries.